Sinus Surgery and Balloon Sinuplasty: What Do Patients Want to Know?. (October 2022) - Fassas, Scott N.; Peterson, Andrew M.; Farrokhian, Nathan; Zonner, Jordan G.; Cummings, Emily L.; Arambula, Zachary; Chiu, Alexander G.; Goyal Fox, Meha
Objective: Limited knowledge exists regarding the information patients seek online about sinus procedures. The goals of our study were to identify the most searched online queries regarding functional endoscopic sinus surgery (FESS) and balloon sinuplasty and evaluate the sources to which patients are directed. Study Design: Observational. Setting: Online Google Database. Methods: Google data were analyzed using the search engine optimization tool Ahrefs. People Also Ask (PAA) questions (extracted from Google searches) helped identify questions for analysis of search query volume. Search results were categorized into specific topics, and the source (eg, academic vs medical practice) of the information was identified. The JAMA benchmark criteria were used to determine the quality of the online resource. Results: The most searched term (average monthly queries) on Google was "sinus surgery" (13, 190), followed by "balloon sinuplasty" (9212). For FESS and balloon sinuplasty, most questions focused on treatment of sinusitis (71.64% vs 79.19%) and preoperative inquiries about sinus issues (11.50% vs 11.35%). Answers to PAA questions for FESS were obtained from academic sources at a higher frequency compared to balloon sinuplasty (26.7% vs 10.3%, P = .016) but a lower frequency from medical practice websites (15.2% vs 29.3%, P = .042). The mean (SD) JAMA scores for FESS and balloon sinuplasty sources were 1.59 (1.46) and 1.40 (1.46), respectively. Conclusion: There is a high volume of online search queries regarding FESS and balloon sinuplasty. The quality of the sources could be improved by addressing authorship, attribution, disclosure, and currency. This information may help otolaryngologists better address patient queries.